Atención de enfermería en pacientes con pie diabético y sus complicaciones. - Ramon Flores, Jennifer Carolina (My University, 2024)
Diabetes mellitus is a chronic degenerative disease with a high risk of severe complications such as diabetic foot, which is the leading cause of amputations due to ulcers. In Ecuador, 66% of patients with diabetes suffer disability as a result of lower limb amputations. Objective: To apply the Nursing Care Process in a patient with diabetic foot and its complications, based on Sister Callista Roy’s Adaptation Model, in order to promote comprehensive adaptation, improve quality of life, and support the prevention of new complications. Methodology: Qualitative, descriptive, and observational approach through clinical history, with informed consent signed. Results: A 66-year-old male patient with a past medical history of type 2 diabetes mellitus and hypertension for approximately 16 years, and surgical history of lower limb amputation due to grade III ulcers with necrosis. He presented with ulceration for more than 7 days on the anterior-lateral plantar region, with bleeding edges and purulent secretion, measuring 3 cm in diameter, along with another ulcer with irregular edges, associated with moist dermal tissue and mild pain. Vital signs: BP 150/80 mmHg, T 37°C, HR 76 bpm, RR 24 bpm, SpO₂ 97%, Glucose 200 mg/dl. Laboratory tests revealed an infectious process with elevated leukocytes: 18.55 x10³/µl. Treatment included antibiotics (clindamycin, amoxicillin + clavulanic acid, ciprofloxacin), daily wound care, and lifestyle education. Conclusion: Adequate assessment by the healthcare professional influenced the patient’s adaptive behavior. Nursing interventions focused on helping the patient cope with and adapt to his illness, strengthening self-esteem, and addressing unmet needs.
La diabetes mellitus es una enfermedad crónica degenerativa con riesgo de complicaciones graves como el pie diabético, principal causa de amputaciones por úlceras. En Ecuador, el 66% de los pacientes con diabetes sufren invalidez por amputaciones de miembros inferiores. Objetivo: Aplicar el proceso de atención de enfermería en un paciente con pie diabético y sus complicaciones, fundamentado en el modelo de adaptación de Sor Callista Roy, con el fin de promover la adaptación integral, mejorar la calidad de vida y favorecer la prevención de nuevas complicaciones. Metodología: enfoque cualitativo, descriptivo, observacional mediante historia clínica con la firma del consentimiento informado. Resultados: Paciente masculino de 66 años con APP: DM2 + HTA hace aproximadamente 16 años y AQx: amputación de las extremidades inferiores por úlceras grado III más necrosis, presenta por más de 7 días ulceración en región plantar anterior lateral bordes sangrantes con secreción purulenta de 3cm de diámetro, se agrega otra ulceración con bordes irregulares, debido a tejido dérmico húmedo y dolor leve, signos vitales TA: 150/80 mmHg, T: 37°C, FC: 76xmin, FR: 24xmin, SO2: 97%, Glc: 200 mg/dl, según exámenes de laboratorio existe un proceso infeccioso por leucocitos elevados: 18.55 x103/ul. El tratamiento incluyó antibióticos (Clindamicina, amoxicilina + ácido clavulánico, ciprofloxacina), curaciones diarias, y educación sobre el estilo de vida. Conclusión: La adecuada valoración del profesional de salud influyó en la conducta adaptativa del paciente. Las actividades de enfermería se enfocaron en ayudar al paciente a afrontar y adaptarse a su enfermedad, fortaleciendo su autoestima y subsanando necesidades.
Keywords: DIABETES MELLITUS; PIE DIABETICO; PATOLOGIA; ULCERA